2019
DOI: 10.1002/cam4.2528
|View full text |Cite
|
Sign up to set email alerts
|

USP9X stabilizes BRCA1 and confers resistance to DNA‐damaging agents in human cancer cells

Abstract: BRCA1, a multifunctional protein with an important role in DNA double‐strand break repair by homologous recombination (HR), is subjected to ubiquitin‐dependent degradation. To date, several E3 ubiquitin ligases have been identified to govern BRCA1 stability, but the deubiquitinase that counteracts its turnover remains undefined. In this study, we report that the ubiquitin‐specific protease 9X (USP9X) is a bona fide deubiquitinase for BRCA1 in human cancer cells. Reciprocal immunoprecipitation assays demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…However, the molecular interplay underlying such clinical effects remains unclear. USP9X has been shown to stabilize BRCA1 and confer resistance to DNA-damaging agents, and yet its downregulation rendered BC cells resistant to tamoxifen, while its up-modulation has been found to promote centrosome amplification, chromosome instability, and higher histologic grades of BC, as well as to enhance Hippo pathway-dependent cell proliferation [ 46 , 47 , 48 , 49 ]. The role of USP7, in turn, appears to be more established in the regulation of DNA replication and mitosis progression by affecting the stability of Aurora-A kinase and Geminin [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular interplay underlying such clinical effects remains unclear. USP9X has been shown to stabilize BRCA1 and confer resistance to DNA-damaging agents, and yet its downregulation rendered BC cells resistant to tamoxifen, while its up-modulation has been found to promote centrosome amplification, chromosome instability, and higher histologic grades of BC, as well as to enhance Hippo pathway-dependent cell proliferation [ 46 , 47 , 48 , 49 ]. The role of USP7, in turn, appears to be more established in the regulation of DNA replication and mitosis progression by affecting the stability of Aurora-A kinase and Geminin [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, USP9X processes function of both oncogene and tumor suppressor, depending on the type and stage of cancer. Recently, it was reported that loss of USP9X function prevented tamoxifen-induced proliferation arrest in estrogen receptor positive breast cancer cells, which suggested that USP9X is closely involved in the endocrine therapy resistance of breast cancer 58,59 . Therefore, the regulatory role of USP9X in tumor is diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, USP9X processes function of both oncogene and tumor suppressor, depending on the type and stage of cancer. Recently, it was reported that loss of USP9X function prevented tamoxifen-induced proliferation arrest in estrogen receptor positive breast cancer cells, which suggested that USP9X is closely involve in the endocrine therapy resistance of breast cancer 58,59 . Therefore, the regulatory role of USP9X in tumor is diverse.…”
Section: Dicussionmentioning
confidence: 99%